Meningkatkan Imunitas Masyarakat Melalui Program Vaksinasi dan Budidaya Tanaman Sansevieria di Desa Limine Barat Kecamatan Tabongo Kabupaten Gorontalo - Nurhayati Tine (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2021)
The Corona Virus (Covid-19) pandemic is endemic in all corners of the world, Indonesia is one of them. To prevent the transmission of COVID-19, the State University of Gorontalo as an educational institution participates in realizing this mission by implementing a community service program, namely Community Service Program by students to rural communities by implementing a program called the Thematic Village Community Service Program. KKN students located in Limehe Barat Village, Tabongo Subdistrict, Gorontalo Regency held an activity related to health aspects, namely vaccination socialization and planting of sansivera flowers. This program aims to prevent the transmission of the corona virus and increase the immunity of the people of West Limehe Village. This program is implemented using four methods, namely observation, socialization, mentoring and training. Based on the survey results, the percentage of vaccines for the people of West Limehe Village only covers 30%. With this health aspect program, the vaccination target of West Limehe Village has reached the target of up to 40% and changed the environment of West Limehe Village to be more beautiful and healthy by planting sansivera flowers.Keywords: Covid-19, KKN, Vaccination, Sansivera